Efektywność techniczna produkcji nasion oleistych w Europie i na świecie - Rusielik, Robert (Technical Efficiency of the Production of Oil Seed Plants in Europe and in the World, 2006)
The article is an attempt to compare the efficiency of production of different species of oil seed plants on the basis of data from selected farms associated in International Farm Comparison Network (IFCN).With the aim to compare the efficiency of this plants production both revenues and costs were converted in the common unit called MtRE (Metric tonne Rapeseed Equivalent) and then technical efficiency for particular plant was computed by applying Data Envelopment Analysis (DEA) method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 285-291